CONTRIBUTION OF R.K. NARAYAN IN THE FIELD OF LITERATURE AND ITS RELEVANCE IN THE MODERN WORLD - M G, Harish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
R.K. Narayan regarded as one of the “Big three” among the Indian novelists in English has been admired for his remarkable gift for telling stories, portraying memorable people of small oddities and eccentricities, and for his humour. To tell a story engagingly is no mean gift for a novelist. Narayan’s fiction rarely addresses political issues or high philosophy. He writes with grace and humor, about a fictional town Malgudi and its inhabitants; and their little lives. Narayan is a classic teller of tales; an enduring appeal springs from his canvas where common men and women of all times and places are joined in their commonalty.